The close association of Muribaculum and PA (10:0/a-17:0) with the occurrence of pancreatic ductal adenocarcinoma and immunotherapy - Wang, Enzhao; Ren, Kuiwu; Wang, Xiangyu; Du, Sen; Gao, Xiang; Niu, Wang; Guan, Chenyue; Liu, Xue; Wu, Panpan; Liu, Chunlong; Yu, Jiangtao; Song, Kun (Frontiers in Immunology, 2024)
BackgroundProgress in immunotherapy for pancreatic ductal adenocarcinoma (PDAC) has been slow, yet the relationship between microorganisms and metabolites is crucial to PDAC development. This study compares the biliary microbiota and metabolomic profiles of PDAC patients with those of benign pancreatic disease patients to investigate PDAC pathogenesis and its relationship with immunotherapy.MethodsA total of 27 patients were recruited, including 15 diagnosed with PDAC and 12 with benign pancreaticobiliary conditions, all of whom underwent surgical treatment. Intraoperative bile samples were collected and analyzed using 16S rRNA sequencing in conjunction with liquid chromatography-mass spectrometry (LC-MS). Multivariate statistical methods and correlation analyzes were employed to assess differences in microbial composition, structure, and function between malignant and benign pancreatic diseases. Additionally, a retrospective analysis was conducted on PDAC patients post-surgery regarding immunotherapy and its correlation with metabolic components.ResultsPDAC patients exhibited a significantly higher abundance of bile microbiota compared to controls, with notable differences in microbiota structure between the two groups (P < 0.05). At the genus level, Muribaculum was markedly enriched in the bile of PDAC patients and was strongly correlated with phosphatidic acid (PA) (10:0/a-17:0). Both of these components, along with the tumor marker CA199, formulated a predictor of PDAC. Furthermore, PA (10:0/a-17:0) demonstrated a strong correlation with PDAC immunotherapy outcomes (Rho: 0.758; P=0.011).ConclusionThese findings suggest that the biliary microbiota and associated metabolites play a crucial role in the development of PDAC and may serve as potential predictive biomarkers and therapeutic targets for disease management.